ECOLOGICAL, TECHNICAL, AND CULTURAL GROUNDS FOR RELOCATING THE V. SAVITSKIY STATE ART MUSEUM OF KARAKALPAKSTAN TO TASHKENT - Rakhmonova , Shakhnoza; Goyibnazarova , Shahnoza (Scientific practical conference, 2025)
This article discusses the issue of relocating the Soviet Museum, located in the region of Karakalpakstan, to the city of Tashkent. The article analyzes the historical and cultural significance of the museum, problems related to its location, and the potential advantages and disadvantages of moving it to the capital. The study presents ideas from the perspective of preserving cultural heritage, transmitting it to younger generations, and promoting tourism. Relocating the museum to Tashkent could increase the number of visitors and stimulate interest in Soviet-era history. However, it is essential to maintain a balance to ensure that the historical spirit of the local environment is not lost during this process.